PERAN GURU DALAM MENANAMKAN KARAKTER RELIGIUS ANAK USIA 5-6 TAHUN DI TK ISLAMIYAH PONTIANAK TENGGARA - Tesa Rahma Wulanda; Aunurrahman Aunurrahman; Marmawi Marmawi (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the teacher's role in inculcating the religious character ofchildren aged 5-6 years in TK Islamiyah Pontianak Tenggara. The research method usedis descriptive method in the form of qualitative research. The subjects in the study wereteachers in the As-salam class and the Al-malik class for children aged 5-6 years at the TKIslamiyah Pontianak Tenggara. Data collection techniques used in this study wereobservation, interviews, and documentation. The results of the study show that: 1. The roleof the teacher as a role model in inculcating children's religious character is directexamples to children. The role of the teacher as a motivator in planting children's religiouscharacter, namely the teacher always gives encouragement to children when children havebehavior that is in accordance with religious teachings, and teachers give rewards for whatchildren have done, 3. The role of teachers as facilitators in character building Children'sreligious education, namely the teacher provides learning facilities for children byproviding facilities to help children in inculcating religious characters, thus the role thatthe teacher has applied for inculcating the religious character of children aged 5-6 yearsin TK Islamiyah Pontianak Tenggara has been well implemented.Keywords: The Role Teacher and Religious Character